New federal initiatives to enhance the medical treatment of opioid dependence. - Fiellin, David A; O'Connor, Patrick G (Annals of internal medicine, 2002)
Opioid dependence is a chronic relapsing medical condition with substantial health and societal complications. Recent federal initiatives are designed to enhance the medical treatment of patients with opioid dependence and will expand the role of internists in the care of these patients. These initiatives include a process for federal exemptions to allow for pharmacologic treatment in office settings, waivers for the use of new medications, and new rules governing the oversight and distribution of opioid agonist medications for maintenance treatment. This perspective describes these initiatives and their implications for internists.
Keywords: Ambulatory Care; Drug Prescriptions; Education, Medical, Continuing; Government Programs; Humans; Legislation, Drug; Narcotics; Opioid-Related Disorders; Research; United States; United States Food and Drug Administration